Diagnostic screening of paroxysmal nocturnal hemoglobinuria: Prospective multicentric evaluation of the current medical indications. Issue 5 (1st October 2016) - Morado, Marta; Freire Sandes, Alex; Colado, Enrique; Subirá, Dolores; Isusi, Paloma; Soledad Noya, María; Belén Vidriales, María; Sempere, Amparo; Ángel Díaz, José; Minguela, Alfredo; Álvarez, Beatriz; Serrano, Cristina; et al.
Abstract : Background: Although consensus guidelines have been proposed in 2010 for the diagnostic screening of paroxysmal nocturnal hemoglobinuria (PNH) by flow cytometry (FCM), so far no study has investigated the efficiency of such medical indications in multicentric vs. reference laboratory settings. Methods: Here we evaluate the efficiency of consensus medical indications for PNH testing in 3, 938 peripheral blood samples submitted to FCM testing in 24 laboratories in Spain and one reference center in Brazil. Results: Overall, diagnostic screening based on consensus medical indications was highly efficient (14% of PNH + samples) both in the multicenter setting in Spain (10%) and the reference laboratory in Brazil (16%). The highest frequency of PNH + cases was observed among patients screened because of bone marrow (BM) failure syndrome (33%), particularly among those with aplastic anemia (AA; 45%) and to a less extent also a myelodysplastic syndrome (MDS; 10%). Among the other individuals studied, the most efficient medical indications for PNH screening included: hemolytic anemia (19%), hemoglobinuria (48%) and unexplained cytopenias (9%). In contrast, only a minor fraction of the patients who had been submitted for PNH testing because of unexplained thrombosis in the absence of cytopenia, were positive (0.4%). Conclusions: In summary, our results demonstrate that the current medical indications for PNH screening by FCM are highly efficient, although improved screening algorithms are needed for patients presenting with thrombosis and normal blood cell counts. © 2016 International Clinical Cytometry Society